EGFR amplification and expression in oral squamous cell carcinoma in young adults. Issue 7 (July 2018) - Costa, V.; Kowalski, L.P.; Coutinho-Camillo, C.M.; Begnami, M.D.; Calsavara, V.F.; Neves, J.I.; Kaminagakura, E.
Abstract: The aim of this study was to investigate epidermal growth factor receptor (EGFR) gene alterations in two groups of patients with oral squamous cell carcinoma (OSCC) (a test group of subjects aged ≤40 years and a control group of subjects aged ≥50 years) and to associate the results with EGFR immunostaining, clinicopathological features, and the prognosis. Sixty cases of OSCC were selected (test group, n  = 21; control group, n  = 39). The tissue microarray technique was applied to ensure the uniformity of results. Gene amplification was analyzed by fluorescence in situ hybridization (FISH), and immunohistochemical staining for EGFR was analyzed using an automated imaging system. EGFR amplification was higher in the test group than in the control group ( P   =  0.018) and was associated with advanced clinical stage ( P   =  0.013), regardless of age. Patients with EGFR overexpression had worse survival rates, as did patients who had T3–T4 tumours and positive margins. EGFR overexpression has a negative impact on disease progression. Despite the higher amplification of EGFR in young adults, it does not significantly impact the survival rates of affected patients.